Isolation of Bioactive Phytoconstituent from Alpinia galanga L. with Anti-Hyperlipidemic Activity. (1st December 2013) - Iyer, Deepa; Sharma, Brajesh K.; Patil, U. K.
ABSTRACT The present study was undertaken to explore the antihyperlipidemic effect of ethanolic extract of rhizomes of Alpinia galanga L. and its chloroform fraction in Triton-induced hyperlipidemic rats. Bioactivity guided fractionation was followed by chromatographic studies. Flash chromatography was done for the most active fraction resulting in the isolation of 5-(hydroxymethyl) furfural. Animals were administered with i.p. injection of Triton WR 1339 at dose of 400 mg/kg body weight. After 24 hr of Triton administration, the ethanolic extract and its fraction were administered orally at doses of 200 and 400 mg/kg body weight in rats. The treatment was continued for 5 days with a view to see the effect on lipid profile. Serum samples were subjected to biochemical analysis. The study dose dependently inhibited the total cholesterol (TC), triglycerides (TG), low-density lipoprotein (LDL) level, and significantly increased high-density lipoprotein (HDL) level. Phytochemical screening revealed the presence of tannins, coumarins, flavanoids, sterols, and glycosides. Phytochemical investigation of the chloroform fraction of A. galanga L. resulted in the isolation of 5-(hydroxymethyl) furfural. UV λmax was found to be 276 nm for the isolated component. Acute treatment caused a stimulatory effect on the HDL level and inhibition in TC and TG elevation induced by triton.